The Influence of Workload and Job Stress on Turnover Intention of PT. Yanmarindo Perkasa Pekanbaru Employees - Suprianto, Joko; Joesyiana, Kiki (Management Science Doctoral Program, Pasundan University, 2023)
The purpose of thisresearchwas tofind out the influence ofworkload and work stress on turnover intention of PT Yanmarindo Perkasa Pekanbaru. The population in this research is the employees of PT Yanmarindo Perkasa Pekanbaru. The sampling technique used by the Census technique, The number of samples used in this research is 154 respondents who are employees of PT Yanmarindo Perkasa Pekanbaru. Questionnaire and literature are used for data collecting, while multiple linear regression analysis, classic assumption test (normality test, heteroscedasticity test, multicollinearity test, autocorrelation test), statistical test (t test, F test, coefficient of determination test) are used as data analysis techniques. The results of this research indicate that workload and work stress have a positive significant effect on turnover intention of employees of PT Yanmarindo Perkasa Pekanbaru either partially or simultaneously.